Effect of hyperlipidemia on the expression of circadian genes in apolipoprotein E knock-out atherosclerotic mice - Hou, Likun (BioMed Central, 2009)
BACKGROUND: Circadian patterns of cardiovascular vulnerability were well characterized, with a peak incidence of acute myocardial infarction and stroke secondary to atherosclerosis in the morning, which showed the circadian clock may take part in the pathological process of atherosclerosis induced by hyperlipidemia. Hence, the effect of hyperlipidemia on the expression of circadian genes was investigated in atherosclerotic mouse model. RESULTS: In apoE-/-mice on regular chow or high-fat diet, an atherosclerotic mouse model induced by heperlipidemia, we found that the peak concentration of serum lipids was showed four or eight hours later in apoE-/- mice, compared to C57BL/6J mice. During the artificial light period, a reduce in circulating level of serum lipids corresponded with the observed increase of the expression levels of some the transcription factors involved in lipid metabolism, such as PPARα and RXRα. Meanwhile, the expression of circadian genes was changed following with amplitude reduced or the peak mRNA level delayed. CONCLUSIONS: Our studies indicated that heperlipidemia altered both the rhythmicity and expression of circadian genes. Diet-induced circadian disruption may affect the process of atherosclerosis and some acute cardiovascular disease.